1996
DOI: 10.3109/00016349609054711
|View full text |Cite
|
Sign up to set email alerts
|

Infertile women with and without endometriosis: A case control study of luteal phase and other infertility conditions

Abstract: Luteal phase defects, sperm abnormalities and myomas are no more common in EAI than in NEI or in advanced stages of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Others [8,9] found significantly higher basal PRL levels in patients with infertility and endometriosis. Brosens et al [4], Matalliotakis et al [19] and Matorras et al [20], however, did not find a significant difference between the groups in terms of basal PRL levels.…”
Section: Discussionmentioning
confidence: 88%
“…Others [8,9] found significantly higher basal PRL levels in patients with infertility and endometriosis. Brosens et al [4], Matalliotakis et al [19] and Matorras et al [20], however, did not find a significant difference between the groups in terms of basal PRL levels.…”
Section: Discussionmentioning
confidence: 88%
“…Based on endometrial biopsies and peripheral hormonal measurements, no difference was found between luteal phases of infertile women with and without endometriosis. 45,46 Our group reported that several cytokines such as MCP-1, IL-8, and growthregulated α (Gro-α) that are elevated in the peritoneal fluid of patients with endometriosis are also elevated in the follicular fluid. [47][48][49][50] The concentration of MCP-1 in the follicular fluid increases with advancing stages of endometriosis.…”
Section: Effects Of Inflammatory Mediators Of Endometriosis On Follicmentioning
confidence: 99%
“…One study showed that the 8 am decline in prolactin levels (seen in healthy women) failed to occur in women with endometriosis [20]. However, Brosens et al [21], Matorras et al [22], Arumugam [23] and Matalliotakis et al [24] did not find a significant difference in basal prolactin levels between the groups.…”
Section: Introductionmentioning
confidence: 99%